Brucella Seroprevalence in a High-Risk Population in Greece: A Cross-Sectional Study - Panagiotis Andriopoulos; Dimitrios Floros; Natalia Gioti; Anargiros Mariolis; Andrea Paola Rojas Gil; Maria Tsironi (Interdisciplinary Perspectives on Infectious Diseases)
Introduction. Brucellosis is a zoonosis with high occupational risk. However, seroprevalence of Brucella antibodies among occupational groups is not known, since studies in endemic countries are rare. Methods. A cross-sectional seroprevalence study was conducted among livestock farmers in an endemic region in Greece. A low-risk group of individuals that just moved in the region was used as controls. Rose Bengal, Wright standard tube agglutination (STA) tests, and specific IgG and IgM antibodies using ELISA were evaluated; differences and odds ratios were calculated. Results were compared with studies from other endemic regions. Results. 100 livestock farmers and family members and 34 first-year students were enrolled. Rose Bengal results were 18% positive versus 0% (p=0.007); Wright STAs for Brucella melitensis were 8% versus 2.9% (p=0.448) and for Brucella abortus they were 2% versus 2.9% (p=0.588). ELISA IgG was positive in 8% of farmers versus 2.9% of students (p=0.448). Parallel testing with Rose Bengal and ELISA IgG was positive in 3% versus 0% (p=0.571). No significant odds ratios were calculated for Wright STAs and ELISA IgG. Conclusions. Healthy livestock farmers may present with positive Rose Bengal test but this translates to true seroprevalence in only a small proportion. Livestock farmers have no significant seroprevalence that may obscure diagnosis of acute brucellosis in clinical settings.